Pest management of social insects in urban settings - Masciocchi, Maité (2017)
Pest management of social insects in urban environments is a growing global concern, given the problems that these pests generate and the growth of urban areas worldwide. In this special issue, we present studies on the management and control of ants, wasps and termites from different areas. Also, we report a global overview on the approaches and efficiency of the different methods used to manage and control them. Current advances on the management of urban social insect pests are promising, yet many challenges remain. We expect that this special issue contributes to shed light on these crucial topics, and brings attention to this challenging and growing problem.